Anti-inflammatory effect of zerumbone on acute and chronic inflammation models in mice. - Sulaiman, Mohd Roslan; Perimal, Enoch Kumar; Akhtar, Muhammad Nadeem; Tengku Mohamad, Tengku Azam Shah; Khalid, Mohamed Hanief; Tasrip, Nor Asmara; Mokhtar, Fuzi; Zakaria, Zainul Amiruddin; Lajis, Nordin; Israf Ali, Daud Ahmad (Elsevier, 2010)
The anti-inflammatory activity of zerumbone (1), a natural cyclic sesquiterpene isolated from Zingiber zerumbet Smith was investigated using carrageenan-induced paw edema and cotton pellet-induced granuloma tissue formation test in mice. It was demonstrated that intraperitoneal administration of 1 at a dose of 5, 10, 50 and 100 mg/kg produced significant dose-dependent inhibition of paw edema induced by carrageenan. It was also demonstrated that 1 at similar doses significantly suppressed granulomatous tissue formation in cotton pellet-induced granuloma test.